The Role of Intellectual Capital In Enhancing The Value Added of The Creative Indus-try In Indonesia In The Digital Era - Maria Yertas (Eduvest - Journal of Universal Studies, 2024)
The digital era brings significant changes across various sectors, including the creative industry. In this era, the creative industry in Indonesia has great opportunities to thrive and enhance its value-added. Intellectual Capital (IC) can be a valuable resource for creating innovative products and services that can increase the value-added of the creative industry. The purpose of this research is to determine the role of Intellectual Capital in enhancing the value-added of the creative industry in Indonesia in the digital era. This research uses a qualitative descriptive method. Data were collected through literature review. The collected data were then analyzed in three stages: data reduction, data display, and conclusion drawing. The results show that intellectual capital plays a role in various important aspects of enhancing the value-added of the creative industry, including enhancing creativity and innovation within the industry, strengthening the competitiveness of the creative industry, assisting in expanding market reach, and improving operational efficiency and effectiveness. Creative industries that effectively manage intellectual capital can achieve significant value-added and success in the continually evolving global market.